VALUATION OF PHYSICAL ACTIVITY IN STUDENTS FROM FIRST TO FOURTH YEAR OF HIGH SCHOOL IN EDUCATIONAL ESTABLISHMENTS WITH THREE DIFFERENT ADMINISTRATIVE DEPENDENCES IN THE CITY OF CHILLÁN, CHILE (Fiep Bulletin - online, 2016)
Perhaps the difficulties in deployment and implementation of public policies on health education, do not reach their goals because of the value they deliver to school this phenomenon. The objective of this study was to measure the level of valuation that deliver physical, educational activity for the first four years of Teaching Medium in three educational establishments of the city of Chillán, Region VIII, Region, "del Bio Bio," Chile. Method: A descriptive, exploratory, non-experimental study; Descriptive analysis is comparative, cross scope and was taken from statistical analysis (normalization compared, statistically significant, comparisons between groups); probabilistic sample of unintentional kind, obtained from three educational establishments, one for each of the administrative offices of the Chilean education: private pay, private subsidized and municipal (public); sample of 204 high school students (68 per educational establishment);the instrument for data collection was Questionnaire Assessment of Physical Activity, established by Campos Gomez, Vilcazán, Arruda, and HespañolCossio-Bolaños (2012), with 11 questions and the main variable is physical activity. Results: men valued more physical activity than women; paid the higher educational establishment showed valuation of physical activity, followed by private subsidized and public order; students between the ages of 17 and 18 years, delivering more value to physical activity. Conclusions: In this study, the educational establishment with higher socioeconomic level, had higher rates of valuation of physical activity; Older students valued more.
Keywords: physical activity; valuation; teenagers.